Utilizing MIKE 21 Software to Create Simple Hydrodynamic Simulations - Subiyanto Subiyanto; Sudradjat Supian (Research Collaboration Community (RCC), 2021)
This paper aim to create simple hydrodynamic simulation by using MIKE 21. The module used in MIKE 21 is LITPACK. LITPACK is one of the modules in MIKE 21 to solve hydraulic and sedimentation problems in coastal areas. Especially in this paper, the LITTLITE engine in LITPACK will be used. LITLINE determines the coastline position using a timeseries of wave climatic data. The model is based on a one-line theory, in which the cross-shore profile is expected to remain unaltered during erosion/accretion, with minor adjustments. Coastal morphology is thus only defined by coastline location (cross-shore direction) and coastal profile at a given long-shore position. The simulation used in this paper is the influence of groins on shoreline dynamics. The results of the simulation show that some areas will experience abrasion and some will experience accretion.